2000
DOI: 10.1577/1548-8659(2000)129<0429:baotfs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic Assessment of Temporal Food Supply and Consumption Demand by Salmonids in the Strawberry Reservoir Food Web

Abstract: This study quantified temporal, spatial, and ontogenetic trophic interactions in Strawberry Reservoir to determine whether salmonid sport fish production was limited by food supply or predation. We combined field data on growth, diet composition, distribution, abundance, survival, and thermal experience with species-specific bioenergetics models for salmonids in Strawberry Reservoir to quantify monthly consumption of all prey fish, Daphnia, and macroinvertebrates. Fish prey represented a minor fraction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 32 publications
2
46
1
Order By: Relevance
“…When Daphnia are not abundant, other large Crustaceans and Copepods increase in the diet (Richards et al, 1975), as can chironomid larvae and pupae (Northcote & Lorz, 1966;Collins, 1971;Richards et al, 1975). In contrast to our results, different size classes (Beacham & McDonald, 1982;Beauchamp et al, 1995;Baldwin et al, 2000) and age classes (Rieman & Bowler, 1980;Leathe & Grahm, 1981;Thiede et al, 2002) of kokanee, excluding fry, have been found to have similar summer-season feeding habits, while feeding habits during other seasons may vary. Beauchamp et al (1995) found that adult kokanee and sockeye in Lake Ozette, WA, fed on Daphnia, insects, and copepods from late summer to early spring, while juveniles fed on Daphnia year round.…”
Section: Food Habitscontrasting
confidence: 95%
“…When Daphnia are not abundant, other large Crustaceans and Copepods increase in the diet (Richards et al, 1975), as can chironomid larvae and pupae (Northcote & Lorz, 1966;Collins, 1971;Richards et al, 1975). In contrast to our results, different size classes (Beacham & McDonald, 1982;Beauchamp et al, 1995;Baldwin et al, 2000) and age classes (Rieman & Bowler, 1980;Leathe & Grahm, 1981;Thiede et al, 2002) of kokanee, excluding fry, have been found to have similar summer-season feeding habits, while feeding habits during other seasons may vary. Beauchamp et al (1995) found that adult kokanee and sockeye in Lake Ozette, WA, fed on Daphnia, insects, and copepods from late summer to early spring, while juveniles fed on Daphnia year round.…”
Section: Food Habitscontrasting
confidence: 95%
“…Regardless of these limitations, our functional response models should be suitable for application in oligotrophic, mesotrophic, or well-mixed systems where kokanee experience zooplankton densities less than 55 Daphnia·L -1 . Whereas the highest prey densities in the majority of the feeding trials were at or above the maximum average Daphnia densities observed in many regional reservoirs (ranging from approximately 5-18 L -1 ; Schneidervin 1985;Baldwin et al 2000;, wild kokanee may seek patches of prey that can have order of magnitude higher densities than the average concentration measured by sampling gear (PinelAlloul 1995;Folt and Burns 1999). Feeding trials at prey densities much higher than the 55 L -1 we used may be necessary to fully define the asymptotic nature of the functional response and accurately predict kokanee feeding rate at very high prey densities.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, lake trout and the commercial fishery represent a demand on the prey fish resource. A commonly used technique to determine if sufficient resources exist to support demand is demand-supply (D-S) analysis (Stewart et al 1983, Ney 1990, Ney 1993, Stewart and Ibarra 1991, Rand and Stewart 1998, Baldwin et al 2000, Johnson and Martinez 2000. D-S analysis combines estimates of prey abundance with predator consumption estimates from bioenergetics models to evaluate carrying capacity limitations (Ney 1990).…”
Section: Introductionmentioning
confidence: 99%